The problem of the formation of skills of students' physical self-improvement in the present conditions of the higher education system - Jhuravel' O.O (Kharkov National Pedagogical University, 2012)
The problem of theoretical and methodical implementation of educational software, educational and recreational objectives of physical education students in self-study exercise. Conducted a survey of specialists of physical education on the mechanisms of formation and maintenance techniques and skills of physical perfection students. A strategy for implementing the principles of full and harmonious physical development of future professionals in the process of self-study, taking into account their interests and needs.